2019
DOI: 10.1183/13993003.00788-2019
|View full text |Cite
|
Sign up to set email alerts
|

European Respiratory Society guideline on long-term management of children with bronchopulmonary dysplasia

Abstract: This document provides recommendations for monitoring and treatment of children in whom bronchopulmonary dysplasia (BPD) has been established and who have been discharged from the hospital, or who were >36 weeks of postmenstrual age. The guideline was based on predefined Population, Intervention, Comparison and Outcomes (PICO) questions relevant for clinical care, a systematic review of the literature and assessment of the evidence using the Grading of Recommendations, Assessment, Development and Evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
123
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(147 citation statements)
references
References 94 publications
0
123
0
10
Order By: Relevance
“…In the symposium on asthma management, it was emphasised that children with asthma should not be treated with a short-acting β-agonist alone [43]. Evidence on the long-term management of children with bronchopulmonary dysplasia is scarce; in the symposium, it was suggested that these children should not be treated with inhaled or systemic corticosteroids and that a multidisciplinary approach for the long-term management of bronchopulmonary dysplasia is needed [44]. For chronic cough in children, it was highlighted that persistent bacterial bronchitis is a common, but often unrecognised, cause of wet cough in children that can be treated with antibiotics [45].…”
Section: Assembly 7: Paediatrics (Sara M Mensink-bout)mentioning
confidence: 99%
“…In the symposium on asthma management, it was emphasised that children with asthma should not be treated with a short-acting β-agonist alone [43]. Evidence on the long-term management of children with bronchopulmonary dysplasia is scarce; in the symposium, it was suggested that these children should not be treated with inhaled or systemic corticosteroids and that a multidisciplinary approach for the long-term management of bronchopulmonary dysplasia is needed [44]. For chronic cough in children, it was highlighted that persistent bacterial bronchitis is a common, but often unrecognised, cause of wet cough in children that can be treated with antibiotics [45].…”
Section: Assembly 7: Paediatrics (Sara M Mensink-bout)mentioning
confidence: 99%
“…We started the therapeutic trial with ICS and betamimetics in case that the persistent respiratory symptoms according to our criteria were observed in an ex‐preterm infant. Though there is no consensus on the therapy with ICS in the long‐term management of CLD 28 and some authorities warned against the unjustified application of ICS, several studies indicated that a chronic inflammatory process might be persistent to late childhood 29‐31 . This leaves open the possibility that a prolonged ICS application after discharge might modify subsequent parameters of lung function test.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for HOT mediated early discharge remain inconsistent across Australia and internationally. The American Thoracic Society guidelines suggest target SaO 2 > 93% and the European Respiratory Society suggesting SaO 2 ≥ 90% . The variations in these positions reflect a gap in evidence as to optimum saturations balanced against the cost of HOT to health care systems.…”
Section: Pulmonary Sequelaementioning
confidence: 99%